Determination of verapamil through LC-ESI-MS/MS in a case of fatal intoxication - Sindy Varón; Diana Mariño (Case Reports)
Verapamil is a synthetic derivative of papaverine, which is used therapeutically as a hypertensive, antiarrhythmic and antianginal. This study describes an analytical method for the determination of verapamil in biological matrices of blood and urine, which consists of a liquid-liquid extraction of samples for analysis using liquid chromatography-mass spectrometry (LC-ESI-MS/ MS), with flurazepam as an internal standard. The method was applied to the acute fatal intoxication of a 17-year-old young woman who consumed 170 tablets of verapamil; the concentration of this medication found in the blood was 18.261mg/L and 0.369mg/L in the urine. This study also puts forth the use of LC-ESI-MS/MS in the analysis of verapamil in biological samples for applications in forensic toxicology.